INOVASI PEMBELAJARAN PAI MELALUI PENDEKATAN OUTING CLASS DI SMA NEGERI 1 SUMBERASIH PROBOLINGGO - wahid, M. Rohul Ulum; M. Jadid Khadavi (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research explains and analyzes Islamic Religious Education (PAI) learning innovations at SMA Negeri 1 Sumberasih which are implemented through the Outing Class approach. SMA Negeri 1 Sumberasih has adopted the Outing Class approach as a strategy to increase the effectiveness of PAI learning. This approach involves using the environment outside the classroom as a learning resource that provides students with direct experience. Implementation methods include planning Outing Class activities that are integrated into the PAI curriculum, involving teachers as facilitators, and evaluating learning outcomes. Evaluation is carried out to ensure that PAI learning objectives are achieved and students gain a better understanding through direct experience outside the classroom. The informants in this research were the Principal, Deputy Head for Curriculum, Deputy Head for Student Affairs, PAI Teacher, and Students. The results of this innovation can make a positive contribution to students' understanding of Islamic teachings and enrich students' learning experiences. It is hoped that the positive implications of the Outing Class approach can be an inspiration for other schools and universities in developing PAI learning at the high school level.